Advancements in photodynamic therapy of esophageal cancer - Bartusik-Aebisher, Dorota; Osuchowski, Michał; Adamczyk, Marta; Stopa, Joanna; Cieślar, Grzegorz; Kawczyk-Krupka, Aleksandra; Aebisher, David (Frontiers in Oncology, 2022)
The poor prognosis of patients with esophageal cancer leads to the constant search for new ways of treatment of this disease. One of the methods used in high-grade dysplasia, superficial invasive carcinoma, and sometimes palliative care is photodynamic therapy (PDT). This method has come a long way from the first experimental studies to registration in the treatment of esophageal cancer and is constantly being improved and refined. This review describes esophageal cancer, current treatment methods, the introduction to PDT, the photosensitizers (PSs) used in esophageal carcinoma PDT, PDT in squamous cell carcinoma (SCC) of the esophagus, and PDT in invasive adenocarcinoma of the esophagus. For this review, research and review articles from PubMed and Web of Science databases were used. The keywords used were “photodynamic therapy in esophageal cancer” in the years 2000–2020. The total number of papers returned was 1,000. After the review was divided into topic blocks and the searched publications were analyzed, 117 articles were selected.